Signposting, a dynamic approach to design process management - Clarkson, PJ; Connor, AM; Melo, AF (Cambridge University Engineering Department, 1999)
This paper presents an overview of a dynamic guidance tool that has been developed to address a need for design support in the aerospace sector. The tool, called signposting, provides the means of directing activity by suggesting the next appropriate task in the design process. This suggestion, based on the presence of key parameters and their associated confidences, allows design to be a reactive process. The underlying logic of the design process is captured using confidence mappings which determine when a task is possible, sensible or not achievable. The lack of prescriptive process structure also allows new design tasks to be added at any time. The signposting technique is described with reference to a simple mechanical design process example.